Trimetazidine with an adjuvant therapy to normalize the circulating visfatin concentration: Future perspective and mechanistic strategies - G. Uma Maheswari; B. Yamini; Ajay Guru; Manikandan Velayutham; V.E. Dhandapani; Kanchana M. Karuppiah; Nicholas Daniel Amalorpavanaden (Journal of King Saud University: Science, 2023)
Visfatin is an adipocytokine that exists in two forms, intracellular and extracellular. Circulating visfatin, which lacks the nicotinamide phosphoribosyltransferase (NAMPT) enzyme activity, functions as adipocytokine. Increased concentration of circulating visfatin is associated with several diseases, including cardiovascular disease. However, therapeutic strategies to normalize the circulating visfatin concentration are less understood. In heart failure (HF) patients with obesity and insulin resistance (IR), the routine HF therapy, trimetazidine (TMZ), which is a sirtuin1 (sirt1) activator, is known to normalize the circulating visfatin concentration. Besides this preferred effect of TMZ, an adjuvant therapy including N-acetylcysteine (NAC, antioxidant and anti-inflammatory molecule), niacin (vitamin B3, NAD + booster) and magnesium (sirt1 activator and anti-inflammatory molecule) can be considered to address the underlying molecular mechanisms that are associated with the pathogenesis of HF. Such mechanisms include excess oxidative stress, increased circulating visfatin concentration, NAD + deficiency, sirt1 down regulation and elevated systemic and cardiac inflammation. Together, the proposition is that TMZ and the suggested adjuvant therapy could improve the clinical symptoms and normalize the circulating visfatin concentration by addressing the underlying mechanisms associated with HF.